MANAJEMEN MUTU PENDIDIKAN DI SD HARAPAN MULIA PADA MASA PANEDMI COVID-19 - Tafonao, Gayus Sadarman (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2022)
Educational quality management is a process of improving educational performance by utilizing available resources to create customer satisfaction. Schools as institutions that provide services in the form of services and products must have quality and existence that can amaze so that it can generate trust among the community. people as customers. This research was conducted at Harapan Mulia Elementary School, Bekasi. The purpose of this study was to determine the management of education quality during the Covid-19 pandemic at Harapan Mulia Elementary School, Bekasi. This research is a descriptive qualitative research, where the data collection process is carried out by means of observation and interviews, the informant in this study to obtain the data and information needed is Mr. Hendra Agatama, S.Pd as the Principal. Based on the results of observations and interviews that have been carried out during the Covid-19 pandemic, Harapan Mulia Elementary School Bekasi has quality management of education that is maintained in quality and even tends to increase in the era of the COVID-19 pandemic. Even though in theera new normal, Harapan Mulia Elementary School still has a high commitment in providing the best service to both students and parents.